Corporate governance and its effect on the efficiency of generating financial performance: evidence from the oil and gas industry of Malaysia - Ong, Tze San; Soh, Wei Ni; Teh, Boon Heng; Ng, Sin Huei (Asia-Pacific Management Accounting Association, Accounting Research Institute & Faculty of Accountancy and UPENA, Universiti Teknologi MARA, 2014)
Capital inflow and joint ventures by investors are very significant in rapidly developing countries, particularly in sectors that require a large capital commitment and high technology support. Therefore, companies will form the most strategic decision to remain competitive in the market to attract and retain investors. Corporate governance and financial performance are important elements considered by investors before they decide on where to place their investment funds. Thus, the study of corporate governance and its effect on the efficiency of financial performance becomes an interesting decision-making tool and is a reference point that assists investors to predict the influence of the corporate governance on the capital they invest. Results of this study show that firm size and CEO/chairman duality significantly influence the efficiency of corporate governance in generating financial performance. Surprisingly, setting risk management committee made no difference in financial performance.